Partial inhibition of complex I activity increases Ca2+-independent glutamate release rates from synaptosomes - DAVEY, GAVIN; Kilbride, Seán M.; Telford, Jayne E.; Tipton, Keith F. (My University, 2008)
Mitochondria have been implicated in the pathogenesis of several neurodegenerative disorders and, in particular, complex I (NADH:ubiquinone oxidoreductase, EC 1.6.5.3) activity has been shown to be partially reduced in postmortem studies of the substantia nigra of Parkinson’s disease patients. The present study examines the effect of partial inhibition of complex I activity on glutamate release from rat brain synaptosomes. Following a 40% inhibition of complex I activity with rotenone, it was found that Ca2+‐independent release of glutamate increased from synaptosomes depolarized with 4‐aminopyridine. Highest rates of glutamate release were found to occur between 60–90% complex I inhibition. A similar pattern of increase was shown to occur in synaptosomes depolarized with KCl. The increase in glutamate release was found to correlate to a significant decrease in ATP. Inhibition of complex I activity by 40% was also shown to cause a significant collapse in mitochondrial membrane potential (Δψm). These results suggest that partial inhibition of complex I activity in in situ mitochondria is sufficient to significantly increase release of glutamate from the pre‐synaptic nerve terminal. The relevance of these results in the context of excitotoxicity and the pathogenesis of neurodegenerative disorders is discussed.
PUBLISHED
Keywords: Complex I; Glutamate release; Mitochondria; Neurodegeneration; Parkinson's disease; Synaptosomes; Neuroscience